Two-dimensional material-assisted remote epitaxy and van der Waals epitaxy: a review - Liu Zhetong; Liu Bingyao; Chen Zhaolong; Yang Shenyuan; Liu Zhiqiang; Wei Tongbo; Gao Peng; Liu Zhongfan (National Science Open, 2023)
Heteroepitaxy can reduce the cost and widen the application range of semiconductor film synthesis and device fabrication. However, the lattice and thermal expansion coefficient mismatches between epilayers and substrates limit the improvement of crystal quality and device performance. Two-dimensional (2D) material-assisted heteroepitaxy offers an effective solution to these challenges. The weak interaction at the interface between films and substrates facilitates the subsequent exfoliation and transfer of epilayer for the fabrication of flexible or high-power electronics. Herein, we summarize the modes of 2D material-assisted epitaxy, which can be classified into remote epitaxy, pinhole epitaxy and van der Waals epitaxy based on the interfacial interaction between the epilayers and substrates. Furthermore, we discuss in detail the improved crystal quality and functional applications, such as flexible devices, wavelength-modulated optoelectronic devices, and thermal management in high-power devices. Moreover, we highlight the challenges and prospects of 2D material-assisted epitaxy, providing roadmaps for lateral research and semiconductor production.